Development of Satisfaction Survey Indicators in Education Bureaucratic Services - Setiawan, Usep; Drajat, Drajat; Hermawan, Agus; Iim Wasliman, HM; Iriantara, Yosal (International Journal of Educational Research & Social Sciences, 2022)
The importance of education in the formation of quality human resources must be followed by the development of the quality of education available in each region. However, until now the development of education in Indonesia is still uneven. One of the government's efforts is to issue a regulation that requires every Indonesian citizen to complete 9 years of compulsory education. So educational services must be followed by good quality educational services as well. This will affect the level of public interest in completing the 9-year compulsory education. The purpose of this study was to determine the current level of education services at the relevant education offices, to be able to respond to community needs and services in the field. By analyzing community satisfaction, the government can improve the quality of education services. By referring to how much the policies and activities of public organizations are needed by the community. Accountability indicators are measured by the ability of officers to achieve service results and benefits, the ability of officers to demonstrate the level of achievement of predetermined targets, the ability of related human resources to carry out service tasks and the ability of officers to solve problems in educational services.